Anthropometric characteristics of early-school age children - Vukićević Veljko; Lukić Nikola; Marinković Marjan; Janjić Nebojša (College of Sports and Health, Belgrade, 2019)
The aim of the study was to determine the current state and potential significant differences in the anthropometric characteristics of boys and girls in the early-school age (7 to 10 years of age). The study group was comprised of 120 respondents, 60 boys and 60 girls of early-school age from the town of Vrbas). Some 30 respondents were assessed from every grade (7, 8, 9, 10 years ± 6 months of age). The measured anthropologic characteristics included height, weight, chest circumference, mid upper arm circumference, mid arm circumference, and triceps, abdominal, subscapular skinfold thicknesses. All measurements were carried out according to the principles of the International Biological Program. A univariant analysis of variance was used to compare the means of different groups. The results of the study indicate that growth and development of children had occurred normally and in a natural flow, according to the natural consequences of cell and tissue growth and division.